Of human kindness : what Shakespeare teaches us about empathy - Cohen, Paula Marantz, 1953- (Yale University Press, 2021)
While exploring Shakespeare's plays with her students, Paula Marantz Cohen discovered that teaching and discussing his plays unlocked a surprising sense of compassion in the classroom. In this short and illuminating book, she shows how Shakespeare's genius lay with his ability to arouse empathy, even when his characters exist in alien contexts and behave in reprehensible ways. Cohen takes her readers through a selection of Shakespeare's most famous plays, including Hamlet, Othello, King Lear, and The Merchant of Venice, to demonstrate the ways in which Shakespeare thought deeply and clearly about how we treat "the other." Cohen argues that only through close reading of Shakespeare can we fully appreciate his empathetic response to race, class, gender, and age. Wise, eloquent, and thoughtful, this book is a forceful argument for literature's power to champion what is best in us.